Pengembangan Media Pembelajaran Berbasis Web Menggunakan Omohage pada Mata Pelajaran Informatika Kelas VIII di SMP Islam Al Fattahiyyah - Anin Nur Ma’idatul Khoiriyah; Bian Dwi Pamungkas (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
This research aims to develop a web-based learning media using the Omohage platform for Grade VIII Informatics subject at SMP Islam AlFattahiyyah. The media was developed to address low student engagement and unsatisfactory learning outcomes, particularly on the topic of The Social Impact of Informatics. The research adopted the Research and Development (R&D) method with the ADDIE development model, consisting of Analysis, Design, Development, Implementation, and Evaluation phases. The developed product is an interactive website featuring structured learning materials, educational videos, interactive quizzes, and user-friendly navigation. Validation by media experts yielded a score of 90.3%, classified as very feasible, while validation by content experts yielded a score of 69.09%, considered adequately feasible. A small-scale trial involving 5 students achieved a score of 90.90%, and a large-scale trial involving 20 students scored 85.66%. The average feasibility rating was 83.99%. Therefore, the Omohage-based web learning media is deemed feasible and effective as an alternative tool to improve student understanding in Informatics. Its use also supports self-directed learning and increases student motivation in digital-based learning environments.